Nilai-Nilai Budaya dalam Legenda Alue Sungai Pinang: Kajian Tradisi Lisan Aceh Barat Daya (Indo-MathEdu Intellectuals Journal, 2026)
The legend of Alue Sungai Pinang is an oral tradition of the people of Aceh Barat Daya that represents cultural values and local wisdom. This research aims to describe and interpret the cultural values contained in the legend based on the theory of cultural value orientation of Kluckhohn and Strodtbeck. This research uses a literary approach with a descriptive-qualitative method. The research data is in the form of legend texts obtained from public speech and written documentation sources. Data collection is carried out through literature studies and documentation, while data analysis includes the process of identifying, classifying, and interpreting cultural values in texts. The results of the study show that the legend of Alue Sungai Pinang contains five cultural value orientations, namely the essence of human life, the essence of human work, the position of humans in space and time, the relationship between humans and nature, and the relationship between humans and others. This finding confirms that legends function as a medium for inheriting cultural values and strengthening the identity of the people of Aceh Barat Daya